2013
DOI: 10.1093/ehjci/jet171
|View full text |Cite
|
Sign up to set email alerts
|

Breathing manoeuvre-dependent changes in myocardial oxygenation in healthy humans

Abstract: In healthy individuals, breathing manoeuvres lead to changes in myocardial oxygenation, which appear to be mediated by CO₂. These changes can be monitored in vivo by oxygenation-sensitive CMR and thus, may have value as a diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 24 publications
2
43
2
Order By: Relevance
“…Several recent studies have used OS-CMR to monitor changes of myocardial oxygenation after changing blood gas levels, especially O 2 and CO 2 . 3,10,11,30 Those studies showed that OS-CMR is a reliable tool to assess the impact of hyperoxia on myocardial oxygenation. 31 Coronary artery stenosis in our animals was verified by an FFR of <0.75.…”
Section: Downloaded From Hyperoxia Worsens Myocardial Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have used OS-CMR to monitor changes of myocardial oxygenation after changing blood gas levels, especially O 2 and CO 2 . 3,10,11,30 Those studies showed that OS-CMR is a reliable tool to assess the impact of hyperoxia on myocardial oxygenation. 31 Coronary artery stenosis in our animals was verified by an FFR of <0.75.…”
Section: Downloaded From Hyperoxia Worsens Myocardial Ischemiamentioning
confidence: 99%
“…It has been shown that it can detect changes in myocardial oxygenation triggered by systemic changes of blood gases, that is, oxygen and carbon dioxide. 10,11 The purpose of this study was to investigate the effect of hyperoxia on myocardial oxygenation and myocardial…”
mentioning
confidence: 99%
“…By exploiting the blood oxygenation level-dependent (BOLD) effect [3], T 2 * sensitized CMR has been proposed as a means of assessing myocardial tissue oxygenation and perfusion. T 2 * mapping has been shown to be capable of detecting myocardial ischemia caused by coronary artery stenosis [4], to reveal myocardial perfusion deficits under pharmacological stress [5][6][7][8][9][10], to study endothelial function [11] or to assess breathing maneuver-dependent oxygenation changes in the myocardium [12][13][14][15]. Preclinical studies have also demonstrated the potential of T 2 * mapping to detect structural changes in the infarcted heart muscle and even to distinguish between focal and diffuse fibrosis [16][17][18].…”
Section: T 2 * Sensitized Cardiovascular Magnetic Resonancementioning
confidence: 99%
“…Breathing maneuvers have been proposed as a physiological vasoactive stimulus leading to consistent myocardial signal intensity changes in oxygenation-sensitive MR images [8,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Mostly related to changes in blood carbon dioxide (CO 2 ), a breath-hold (leading to hypercapnia with a net increase of blood CO 2 ) is an effective vasodilator, whereas hyperventilation with hypocapnia causes vasoconstriction [8,[20][21][22]. By combining these maneuvers, the achievable changes in pCO 2 are increased, resulting in a more extended range in vascular resistance with greater changes in OS signal intensity Because of an abnormal coronary vascular response in patients with OSAS, we hypothesized that the coronary vascular response to hyperventilation and long breath-hold is diminished in patients with OSAS when compared to healthy volunteers, as reflected by changes in myocardial oxygenation during voluntary apnea following hyperventilation.…”
Section: Introductionmentioning
confidence: 99%